2002
DOI: 10.1109/tns.2002.801666
|View full text |Cite
|
Sign up to set email alerts
|

Summary and outlook of the international workshop on aging phenomena in gaseous detectors (DESY, Hamburg, October 2001)

Abstract: High Energy Physics experiments are currently entering a new era which requires the operation of gaseous particle detectors at unprecedented high rates and integrated particle fluxes. Full functionality of such detectors over the lifetime of an experiment in a harsh radiation environment is of prime concern to the involved experimenters. New classes of gaseous detectors such as large-scale straw-type detectors, Micro-pattern Gas Detectors and related detector types with their own specific aging effects have ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…A detailed discussion of aging phenomena is beyond the scope of this paper. The achievements of past R&D projects are summarized in [68,69,70,71], the most recent developments in radiation hardness research with state-of-the-art gaseous detectors are reviewed in [72,73,74]. Detailed studies of micro-pattern GEM and Micromegas concepts have revealed that they might be even less vulnerable to radiation-induced performance degradation in harsh radiation environments than standard silicon microstrip detectors.…”
Section: Radiation Hardness Of Gaseous Detectorsmentioning
confidence: 99%
“…A detailed discussion of aging phenomena is beyond the scope of this paper. The achievements of past R&D projects are summarized in [68,69,70,71], the most recent developments in radiation hardness research with state-of-the-art gaseous detectors are reviewed in [72,73,74]. Detailed studies of micro-pattern GEM and Micromegas concepts have revealed that they might be even less vulnerable to radiation-induced performance degradation in harsh radiation environments than standard silicon microstrip detectors.…”
Section: Radiation Hardness Of Gaseous Detectorsmentioning
confidence: 99%
“…The achievements of past R&D projects in gas detectors are excellently summarized in [1][2][3][4], new developments in the radiation damage research have been reviewed at the 'International workshop on Aging Phenomena in Gaseous Detectors' held at DESY, Hamburg in October, 2001 [5,6]. A great effort has resulted in the optimization and construction of large systems of gas detectors for intense hadron beams, depending on the need for the best spatial resolution (MPGD), best timing resolution for trigger (Resistive Plate Chambers (RPC), MPGD), high-rate tracking and particle identification (straw-type detectors and multi-wire proportional chambers (MWPC)) and single photon detection (CsI-GEM photodetectors).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge accumulated since the first workshop was summarised at the second international workshop on "Aging Phenomena in Gaseous detectors" held at DESY in the year 2001 [7]. The present article is largely based on results reported at this workshop and on several excellent comprehensive reviews of this subject [8][9][10][11]. Measured and expected particle rates as a function of radial distance to the beam axis for various experimental conditions.…”
mentioning
confidence: 99%